2018
DOI: 10.30881/jogps.00016
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of asphaltene entity, precipitation, and deposition, introducing recently models of deposition in the well column

Abstract: Organic precipitations are highly sticky and hard if some asphaltenes are present. This causes a deposition problem to occur when thermodynamic conditions are suitable for sedimentation in a wide range of production processes. This range may start from the porous media around the oil well and continue to the production pipes. Asphaltene exists in many light and heavy oil reservoirs, which often causes problems in the process of crude oil production. Asphaltenes have up to hundreds of carbon molecules in its st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…The recent increase in the number of scientific publications [61][62][63][64][65][66][67][68][69] devoted to a detailed analysis of various approaches to modeling RAC by world scientists proves the importance and prospects of developing improved mathematical models for predicting RAC.…”
Section: Association Modelmentioning
confidence: 99%
“…The recent increase in the number of scientific publications [61][62][63][64][65][66][67][68][69] devoted to a detailed analysis of various approaches to modeling RAC by world scientists proves the importance and prospects of developing improved mathematical models for predicting RAC.…”
Section: Association Modelmentioning
confidence: 99%
“…Finally, in downstream where crude oil is refined, since instability of asphaltenes may lead to coking, fouling, and deactivation of the catalysts used in the different refining processes. 8,16 Despite the fact that crude oils own a complex composition, compounds in crude oils can be grouped into four main fractions designated as SARA: saturated, aromatic, resin, and asphaltenes. Regarding their capacity to keep asphaltene in a solubilized state, saturated compounds are considered nonsolvent, while resins and aromatics are solvents.…”
Section: Introductionmentioning
confidence: 99%
“…An important concern when processing heavy crude oils by catalytic hydrotreating/hydrocracking is sediment formation. It has been reported that during hydrotreating, the most important factors responsible for the generation of sediments are aromaticity and polycondensation of aromatics, as well as the solubility of asphaltenes in resins. …”
Section: Introductionmentioning
confidence: 99%
“…Los asfaltenos son considerados como compuestos polares, lo que es causado por los electrones de átomos como el azufre, el oxígeno y el nitrógeno (Hasanvand et al, 2018). Se ha determinado que, incluso en bajas concentraciones, la molécula de asfaltenos presenta tendencia a agregarse y precipitarse, lo que causa grandes daños en las diferentes etapas del procesamiento del petróleo, como consecuencia de obstrucciones ocasionadas por los depósitos orgánicos que producen (Guzmán et al, 2017;Hasanvand et al, 2018).…”
Section: Introductionunclassified
“…Los asfaltenos son considerados como compuestos polares, lo que es causado por los electrones de átomos como el azufre, el oxígeno y el nitrógeno (Hasanvand et al, 2018). Se ha determinado que, incluso en bajas concentraciones, la molécula de asfaltenos presenta tendencia a agregarse y precipitarse, lo que causa grandes daños en las diferentes etapas del procesamiento del petróleo, como consecuencia de obstrucciones ocasionadas por los depósitos orgánicos que producen (Guzmán et al, 2017;Hasanvand et al, 2018). La formación de depósitos de asfaltenos es un problema de importancia en la producción de petróleo, porque el depósito de asfaltenos perjudica la recuperación y la producción, al producir reducción de la permeabilidad de la roca del yacimiento y disminución del diámetro efectivo de los punzonados en la tubería de producción, lo que restringe el flujo de petróleo (Martins, Martins y Santos, 2018).…”
Section: Introductionunclassified